Knowledge and practices towards road safety measures among intern and resident doctors: a cross-sectional study - Das, Bishnu Ram; Bora, Sampurna; Das, Arpan Kumar; Kakoti, Gitali (International Journal Of Community Medicine And Public Health, 2021)
Background: In spite of ongoing commitment and efforts, road traffic accidents continue to be a leading cause of death and disabilities in India. Adequate knowledge on road safety measures among budding doctors can create awareness and provide preventive counselling to their clients. An attempt was made to assess the knowledge and practices about road safety measures among intern and resident doctors working in tertiary care setting. Methods: An institution based cross-sectional study was conducted among 168 young doctors of Jorhat Medical College, Jorhat, Assam. Results: Among the enrolled study participants 54% were intern and 46% were resident doctors. More than half of the participants were male. Knowledge on different, road signs among the young doctors ranges in between 68% to 99%. The dangerous effects of alcohol consumption while driving/riding were known to 93% of the participants. While riding two wheels, only 58% always use helmet with belt and 33% sometimes use mobile phone. Regarding exceed in speed limit in two wheels, 11 (17%) participants informed that they surpass the speed limit and among them 10 (26%) were males which was found to be statistically significant. Among four-wheelers, 48% always use seat belt and 49% sometimes use mobile phone while driving. During four-wheel driving, 21% participants were involved in occasional drinking/smoking and it was found significantly higher in males. Conclusions: The study revealed that in spite of having adequate knowledge about road safety measures, intern and resident doctors are poor in practicing which warrant motivational and counselling intervention.